Thin Capitalization Rules, Capital Structure, Tax Avoidance, and the Covid-19 Pandemic: Evidence from Indonesian Listed Firms - Faisal Faisal; Arifin Rosid (Journal of International Conference Proceedings (JICP), 2022)
In 2015, the Indonesian Government issued a regulation regarding thin capitalization rules, which was applied in 2016. This study generally aims to test and analyze the effectiveness of thin capitalization rules in reducing tax avoidance measures in Indonesia, especially for listed companies. The effect of thin capitalization rules is divided into two types: the influence on the company's capital structure (direct impact) and corporate tax avoidance (indirect impact). The test was carried out using a regression method with a difference-in-difference (DiD) approach in proving causal inference between the studied independent and dependent variables. Furthermore, this research will also discuss the moderating effect of the financial crisis due to the Covid-19 pandemic. The selection of samples uses purposive sampling techniques, where the samples are companies listed on the Indonesia Stock Exchange from 2011 to 2020. The regression results indicate that implementing thin capitalization rules negatively affects companies' capital structure but does not affect their tax avoidance level. The results also confirm that the economic crisis caused by the Covid-19 pandemic moderates the influence of thin capitalization rules on capital structures and tax avoidance levels of enterprises. The findings are expected to offer relevance, particularly to the Indonesian tax authority, concerning the effectiveness of the thin capitalization rules in minimizing the possibility of tax avoidance. Keywords: Capital Structure, Covid-19 Pandemic, Public Companies, Tax Avoidance, Thin Capitalization Rules.